INTEGRASI ANALISIS PRODUCT LIFE CYCLE DAN METODE AHP-TOPSIS DALAM PERUMUSAN STRATEGI PENGEMBANGAN PRODUK - Imam Santoro TIP (Jurnal Teknologi Industri Pertanian, 2016)
Product development is one of the effort of enterprises for competing. One of the way that can be used is product life cycle analysis. The objective of this research was to formulate strategy for the product development by applying product life cycle (PLC) analysis and Analytical Hierarchy Process- Technique for Order of Preference by Similarity to Ideal Solution (AHP-TOPSIS). The analysis of PLC was used to determine product position in competitive environment. Next steps was analysing and choosing strategy alternative by AHP-TOPSIS method. The result of study showed that the integration PLC analysis with AHP-TOPSIS method could be used to formulate the strategy of product development comprehensively. The result of PLC analysis on the UKM X showed that position of product was in growth phase. The result of AHP-TOPSIS analysis showed factor with the highest priority for considering in formulating strategy of product development was consumer preferences (0.370) and cost of production (0.24). The operational strategy for supporting business expansive was creating promotion effectively (0.542) and improving product quality (0.510).Keywords: AHP-TOPSIS, product development, PLC, strategy